TRENDS IN PESANTREN EDUCATION ISSUES IN BUILDING MILLENNIAL CHARACTER - Ataman, Abdullah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze and understand the trend of pesantren education issues in character building at the Ulil Albab Islamic Boarding School which is a boarding school that educates and fosters the character of students. This research uses qualitative research with the type of case study. The informants in this study were the caregivers of islamic boarding schools were kyai, ustadz / ustadzah and students in the islamic boarding school environment. The results of the research on the challenges that must be faced by students are as follows: first, the uswah factor. Exemplary and role model for students in Islamic boarding schools. Second, Double Personality or split personality. Third, Cultural Differentiation and different student personalities are one of the ways to communicate. Fourth, Impact Technology. Aware of advances in technology and information for students so as not to be left behind.